ANALYSIS OF FACTORS INFLUENCING THE INCOME GENERATED BY INFORMAL FRESH PRODUCE TRADERS DURING COVID-19 PANDEMIC IN POLOKWANE LOCAL MUNICIPALITY, SOUTH AFRICA - Mapula Hildah Lefophane; Maria Sherly Mdungwa; Isaac Busayo Oluwatayo (International Journal of Food and Agricultural Economics, 2022)
This study examined factors influencing income generated by 100 informal fresh produce traders in Polokwane Local Municipality during the COVID-19 pandemic in South Africa. An Ordered Probit Model was used to examine the extent to which several factors had affected traders’ income, measured on a 5-Point Likert Scale ranging from “very low income” to “very high income”. The descriptive results showed that none of the traders had generated “very high income”, which is attributable to COVID-19 regulations and restrictions. The empirical results showed that age, education levels, other sources of income, government support, social relief grant, trading license, trading status, time period of contract, and trading stall, increased the probability of generating higher income. These results serve to inform policymakers on the policy strategies to pursue in order to improve the income generated by the informal fresh produce traders.